High Fibrinopeptide A (FPA) Levels in Acute Non-Lymphocytic Leukemia Are Reduced by Heparin Administration - Gugliotta, L; Viganò, Silvana; D’Angelo, A; Guarini, Anna; Tura, S; Mannucci, P M (Thrombosis and Haemostasis, 1984)
Plasma levels of fibrinopeptide A (FPA) in 30 untreated patients with acute non-lymphocytic leukemia (ANLL) were significantly higher than in 30 healthy controls (p <0.001). Patients without laboratory signs of disseminated intravascular coagulation (DIC) had levels of FPA higher than controls (p <0.02) but markedly lower than patients with DIC (p <0.001). Five patients with M3 leukemia had a higher mean FPA level (p <0.02) and a lower peripheral blast cell count (p <0.05) than patients with other cytological subtypes of ANLL. When patients with M3 were excluded, a significant correlation was observed between the peripheral blast cell counts and the FPA levels (r = 0.66, p <0.001). FPA levels were similar with body temperature either above or below 38° C. After intravenous bolus of heparin FPA dropped to normal levels in 14 out of 17 patients who had high baseline values. These findings indicate that intravascular thrombin formation, which probably result from the expression of procoagulant activities of blast cells, is the main cause of high FPA in the majority of patients with acute non-lymphocytic leukemia.
Keywords: Fibrinopeptide A (FPA); Acute leukemia; Heparin